Keberagaman Gender Dewan Direksi Terhadap Kinerja Organisasi - Prestiani, Tri Sangga; Mujtaba, Muhammad Irsyad Elfin; Primasatya, Rieswandha Dio; Lorensa, Like (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to identify patterns in studies related to gender diversity in the composition of boards of directors and its impact on company performance for the last 10 years. The research approach used is library research, utilizing data from the Scopus database with a total of 839 articles. Data analysis was conducted using VOSviewer software version 1.6.20. The data processing results indicate that research on gender diversity and company performance often uses keywords such as industrial performance, performance, corporate governance, firm performance, diversity, and gender diversity. Frequently cited documents discuss gender diversity in boards, corporate policies, corporate risks, climate change risks, CSR, ESGD, environmental performance, innovation, workplace diversity, demographics, inclusive leadership, big data usage, empowering leadership, employee performance, work engagement, creativity, decision making unit heterogeneity, gender awareness in academia, and emotional intelligence. Documents frequently cited together in the article reference lists include those related to women in board seats and their influence on corporate governance, Agency Theory, CSR, corporate reputation, Upper Echelons Theory, and external constraints on companies. This research has implications, especially for the academic community, in understanding future research agendas. Additionally, the findings can be considered in decision making processes related to board diversity based on previous research studies. This bibliometric study provides an overview of future research opportunities related to board diversity and organizational performance.